2011
DOI: 10.1128/jb.05467-11
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis Extracytoplasmic Function σ Factor σ V Is Induced by Lysozyme and Provides Resistance to Lysozyme

Abstract: Bacteria encounter numerous environmental stresses which can delay or inhibit their growth. Many bacteria utilize alternative factors to regulate subsets of genes required to overcome different extracellular assaults. The largest group of these alternative factors are the extracytoplasmic function (ECF) factors. In this paper, we demonstrate that the expression of the ECF factor V in Bacillus subtilis is induced specifically by lysozyme but not other cell wall-damaging agents. A mutation in sigV results in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(136 citation statements)
references
References 49 publications
5
129
2
Order By: Relevance
“…lmo2473 encodes an uncharacterized protein that has been hypothesized to function in the synthesis of peptidoglycan precursors (36), and lmo2768 encodes an uncharacterized membrane protein with an ABC transporter domain. lmo0540 (here referred to as pbpX) is the homolog of pbpX in B. subtilis, where it contributes to lysozyme resistance (37). pbpX encodes a ␤-lactamase domain; however, it has been reported that in Mycobacterium smegmatis, PbpX does not contribute to ␤-lactam antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…lmo2473 encodes an uncharacterized protein that has been hypothesized to function in the synthesis of peptidoglycan precursors (36), and lmo2768 encodes an uncharacterized membrane protein with an ABC transporter domain. lmo0540 (here referred to as pbpX) is the homolog of pbpX in B. subtilis, where it contributes to lysozyme resistance (37). pbpX encodes a ␤-lactamase domain; however, it has been reported that in Mycobacterium smegmatis, PbpX does not contribute to ␤-lactam antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
“…subtilis also contains pbpX, oatA, and the genes for multiple peptidoglycan deacetylases (13,37,61), yet B. subtilis is not a pathogen and is significantly more sensitive to lysozyme than L. monocytogenes. The MIC of lysozyme is 6 g/ml for WT B. subtilis (13) and 2,000 g/ml for L. monocytogenes (data not shown).…”
Section: Figmentioning
confidence: 99%
“…The oligonucleotides used for eglS expression (Fwd-GTTCACACGGATTGCAATGG, rev-TACATCGCTGCACGGAAAAC) were designed with Primer3 plus (Untergasser et al 2012) using the eglS gene from B. subtilis 168 (Barbe et al 2009). The rpoB gene was selected as a reference gene for normalization (Ho et al 2011). In order to evaluate the reproducibility of the reaction, a calibration curve was prepared using 1000, 100, 10, 1, and 0.1 ng of cDNA from a control sample and 200 nmol/L of each oligonucleotide from the reference gene according to Nolan et al (2006).…”
Section: Rna Extraction and Rt-qpcrmentioning
confidence: 99%
“…The genes for the σ factors and the anti-σ factors form operons whose transcription is directed by the cognate σ factors; the activities of the promoters for ECF σ factor genes are thus indicative of the activities of the respective ECF σ factors [1] [2] [3]. Among these ECF σ factors, σ V primarily responds to lysozyme [4]. It is activated by stepwise proteolytic destruction of the anti-σ factor RsiV via regulated intramembrane proteolysis (RIP) [5].…”
Section: Introductionmentioning
confidence: 99%